Sequelae of COVID-19 in Hospitalized Children: A 4-Months Follow-Up. Issue 12 (December 2020) - Denina, Marco; Pruccoli, Giulia; Scolfaro, Carlo; Mignone, Federica; Zoppo, Marisa; Giraudo, Isaac; Silvestro, Erika; Bertolotti, Luigi; Rosati, Sergio; Ramenghi, Ugo; Garazzino, Silvia
Abstract : Little is known about the sequelae of SARS-CoV-2 infection in children. In a COVID-19 dedicated clinic, we followed-up for 4 months 25 children previously hospitalized for COVID-19, performing clinical, laboratory, and lung ultrasound evaluation. Mid-term sequelae were rarely observed in our COVID-19 children's cohort.